2013
DOI: 10.1098/rsbl.2012.0806
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and elevational diversity capacity: do weedy species take up the slack?

Abstract: Climate change leads to species range shifts and consequently to changes in diversity. For many systems, increases in diversity capacity have been forecast, with spare capacity to be taken up by a pool of weedy species moved around by humans. Few tests of this hypothesis have been undertaken, and in many temperate systems, climate change impacts may be confounded by simultaneous increases in human-related disturbance, which also promote weedy species. Areas to which weedy species are being introduced, but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…This may also favour range expansions of invasive species to higher altitudes from which they are currently excluded because of low‐temperature extremes (le Roux et al., ). Indeed, there is already evidence of range expansions of invasive species to higher altitudes since 1965 (Chown et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This may also favour range expansions of invasive species to higher altitudes from which they are currently excluded because of low‐temperature extremes (le Roux et al., ). Indeed, there is already evidence of range expansions of invasive species to higher altitudes since 1965 (Chown et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies occurring along the same elevational gradients and across multiple sampling periods will be particularly beneficial (Fig. S2; Seipel et al., ; Chown et al., ; Marini et al., ). For example, in this study, despite similar sampling approaches (methods, time and location), non‐native and native plants exhibit clearly different elevational diversity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Second, evidence is mounting of the upward spread of non‐native species (e.g. Alexander, Naylor, Poll, Edwards, & Dietz, ; Alexander et al., ; Arevalo et al., ; Averett et al., ; Chown et al., ; Loarie et al., ; Pauchard et al., ; Seipel et al., ; Zhang et al., ), likely a consequence both of climate change and of changing land use associated with growth in human activities (Alexander et al., ; Jakobs, Kueffer, & Daehler, ; Marini, Gaston, Prosser, & Hulme, ). Therefore, much interest exists in understanding how these changes in non‐native elevational ranges may impact native species and communities.…”
Section: Introductionmentioning
confidence: 99%
“…An emphasis is now on sustainable use of water, equitable allocation and protection of water resources at global scales (Bogardi et al ., ), indicating the importance of water accounting and water savings projects. Recent research also suggests that in non‐water‐limited environments (perennial streams and rivers) the rate of spread of non‐native, invasive weed species will increase (Chown et al ., ). The research reported here provides water resource managers with a method to improve basin‐wide accounting of water losses from riparian systems resulting from the introduction and spread of invasive weeds.…”
Section: Discussionmentioning
confidence: 97%